Foreign Bodies Inhalation - Hussain, Abdulameer M. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: foreign bodies Inhalation still a common problem in Iraq, occurring in both lay and professional segments of our society. Their successful removal is based on a collected experience of our thoracic surgical teams.Patients&Methods: A prospective study of two hundred forty eight patients referred to the department of thoracic surgery of the surgical subspecialties hospital of the medical city teaching complex during the year (2007) due to witnessed or suspicion of foreign body inhalation. Patients were grouped into group 1 with definite history of foreign body inhalation and group 2 with no such history.Results: In group 1, out of 203(81.85%) patients, about 169(83.25%) patients were proved to have foreign body inhalation by rigid bronchoscopy, while in group 2,foreign body inhalation were proved in 14(31.11%) patients out of 45(18.14%) patients. The commonest age group of foreign body Inhalation was 6 months - two years (63.93%), and males to female ratio was 1.8:1. The highest peaks were encounter in July and August. The results of chest X-ray were normal in (53.55%) of cases and the most common radiological abnormality was pneumonic consolidation which was seen in (15.84%) of cases. Organic foreign bodies were representing (86.3%), the commonest organic foreign body was watermelon seed (48.65%), and the common site of foreign body lodgment was the right main bronchus.Conclusion: The mere suspicion of a foreign body Inhalation is a justification for bronchoscopy. A negative bronchoscopy is better than to leave it inside with its serious sequels.